Brytyjscy Polacy – polscy Brytyjczycy: osiągnięcia młodego pokolenia emigracyjnego w zakresie języka ojczystego na podstawie analizy egzaminu General Certificate of Secondary Education (Polish) - Łączek, Marcin (Neofilolog, 2017)
The article concentrates on achievements of the younger generation of emigrants in the mother tongue based on an analysis of General Certificate of Secondary Education (Polish). At its beginning, the author lays out some of the issues concerned with bilingual glottodidactics and Polish education abroad (the latter is presented in an exolingual context; here: based on England). In the further course, a reference is made to English educational system with a particular stress put on Key Stage 4 examinations, that is General Certificate of Secondary Education (here: in Polish). The data gathered come from one of the AQA centres in which the author of the present text worked.